ANALISIS PENGARUH NILAI SAHAM YANG BEREDAR, STRUKTUR MODAL, RISIKO PASAR, DAN SUKU BUNGA TERHAD AP RETITRN SAHAM DI BEJ DENGAN PENDEKATAN MODEL DINAMIS (Studi Kasus Pada Sektor Aneka lndustri Tahun 1996-2002) - Ari Christianti; Murti Lestari (Fakultas Bisnis UKDW, 2005)
The study aims at empirically proving and analyzing the balance model of Capital Asset Pricing Model (CAPM with the multifactor of risks, consisting of: outstanding stocks value, capital structure represented by Debt EquiQ Ratio (DER), market risk as represented by stock market beta, and the interest rate on company return on stock.This research uses a dynamic model approach considering the existence of the weaknessesin a classic linear model. Since the investment is related to investors behavior that need a lag to market change, the use of the dynamic model approach will be better. It is because the dynamic model uses autoregressive approach containing the lag. The dynamic model used here is Partial Adjustment Model (PAM) and Error Correction Model (ECM). Based on the estimation of the PAM model it is proven that the model is inefficient in finding the evidence confirming the hypothesis. Subsequently,based on the result of the examination of the ECM model it isconcluded that outstanding stocks value has a positive and signiJicant impact in short term and a negative impact in long term. It means that in the short term outstanding stocks value serves as the consideration for investors in making an investment. However in the long term they are likely to believe that the use of smaller internal capital proportion will be more beneficial for them. The capital structure has only a longierm impact on the return on stock. It means that the impact of DER on stock return on miscellaneous industry sector needs the quite long lag to influence the investors in determining stocks return. It indicates that in the long term they believ:e that the use of increasing number of loan will causes the decrease in company liquidity. Consequently, the opportunity for the company to go bankrupt is bigger Beta stock in the study has a negative impact in the long term. Theoretically, it is not consistent with the parameter direction and indicated that beta stock does notserve as an app;r,pviate prory in measuring the rislcs on. miscellaneous industry sector The interest rate has in the long term a negative impact on stocks return and needs the long lag to influence the investors in determining the return on stocks.Keywords: Stock return, outstanding stock value, DER (Debt Equity Ratio), beta, interest rote, ECM (Eruor Correction Model)